2023
DOI: 10.1186/s13059-022-02845-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics unveils xylem cell development and evolution

Abstract: Background Xylem, the most abundant tissue on Earth, is responsible for lateral growth in plants. Typical xylem has a radial system composed of ray parenchyma cells and an axial system of fusiform cells. In most angiosperms, fusiform cells comprise vessel elements for water transportation and libriform fibers for mechanical support, while both functions are performed by tracheids in other vascular plants such as gymnosperms. Little is known about the developmental programs and evolutionary rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 113 publications
1
30
0
1
Order By: Relevance
“…However, many studies have reported the discrepancy on tissue development and orthologous gene expression patterns between Arabidopsis and other species [ 4 , 5 ]. Take xylem development for example, Arabidopsis lacks one xylem cell type (ray parenchyma) and the development of another xylem cell type (libriform fiber) is incomplete with respect to woody eudicots [ 6 ]. The expression patterns of many genes involved in xylem development are also different between Arabidopsis and other woody species, such as Populus [ 4 6 ].…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many studies have reported the discrepancy on tissue development and orthologous gene expression patterns between Arabidopsis and other species [ 4 , 5 ]. Take xylem development for example, Arabidopsis lacks one xylem cell type (ray parenchyma) and the development of another xylem cell type (libriform fiber) is incomplete with respect to woody eudicots [ 6 ]. The expression patterns of many genes involved in xylem development are also different between Arabidopsis and other woody species, such as Populus [ 4 6 ].…”
Section: Main Textmentioning
confidence: 99%
“…Take xylem development for example, Arabidopsis lacks one xylem cell type (ray parenchyma) and the development of another xylem cell type (libriform fiber) is incomplete with respect to woody eudicots [ 6 ]. The expression patterns of many genes involved in xylem development are also different between Arabidopsis and other woody species, such as Populus [ 4 6 ]. This functional and developmental diversity underscores the risks of using Arabidopsis marker genes for cell type annotation in woody eudicots.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…The most remarkable observation is the presence of two types of cambium‐like cell pools within secondary vascular tissues, which provides a new perspective on vascular cambium initiation during wood development (Du et al, 2023; Li et al, 2023). The developmental lineages of ray and fusiform cells in developing xylem were determined by single‐cell and laser capture microdissection transcriptome profiling on four divergent woody angiosperms representing core and base eudicots (Tung et al, 2023). Furthermore, small conditional RNA sequencing data can be used to forecast gene redundancy during the wood‐forming process (Chen et al, 2021).…”
Section: Understanding Of Wood Formationmentioning
confidence: 99%